Electrical Stimulation of the Lower Esophageal Sphincter to Treat Gastroesophageal Reflux After POEM. (August 2018) - Rieder, Erwin; Paireder, Matthias; Kristo, Ivan; Schwameis, Katrin; Schoppmann, Sebastian F.
As per-oral endoscopic myotomy (POEM) is not followed by any anti-reflux procedure, a common concern is the risk of postoperative gastro-esophageal reflux disease (GERD). Electrical stimulation of the lower esophageal sphincter (LES-EST) could be an option for post-POEM GERD. A 68-year old male obese patient underwent successful POEM but developed GERD not responsive to proton pump inhibitors. Consecutively, the patient had implanted an electrical LES stimulation device, consisting of bipolar LES-electrodes connected to a subcutaneous pulse generator. POEM reduced the Eckardt score (9 vs. 0), the LES resting pressure (52.0 vs. 16.4 mmHg), and the Integrated Relaxation Pressure (62.0 vs. 10.0 mmHg). LES-EST substantially reduced post-POEM GERD symptoms. GERD-HRQL scores indicated the elimination of heartburn (26 vs. 7) and regurgitation (24 vs. 3) at three months. A reduced total number refluxes (82 vs. 14) was observed. The %-time of pH below 4 was only slightly reduced (8.6% to 6.2%).LES-EST appears to be a feasible option to symptomatically treat post-POEM GERD for patients not ideal for conventional anti-reflux surgery.